ANALISIS PERBANDINGAN PERFORMA FHRP PADA ROUTING EIGRP MENGGUNAKAN IPV4 DAN IPV6 - Wahyudi, Sandi; Destya, Senie (The Indonesian Journal of Computer Science, 2024)
The limited capacity of IPv4, which only supports about 4.3 billion unique addresses, necessitated the development of a larger addressing system. IPv6 was developed to overcome this limitation, providing a wider range of addresses and improving address management and security. In a reliable and efficient network, mitigating failures and errors that can degrade Quality of Service (QoS) is important. QoS ensures that networks that require reliability, high bandwidth, or low latency can function optimally. One method to overcome network failures is to use First Hop Redundancy Protocol (FHRP), such as HSRP (Hot Standby Router Protocol) and GLBP (Gateway Load Balancing Protocol). This research shows that GLBP on IPv6 provides the best network performance compared to other protocols. GLBP on IPv6 achieves the highest throughput of 93,95130523 Bytes and the lowest delay of 1,000519298 seconds under normal conditions. In addition, under fault conditions, GLBP on IPv6 has the lowest downtime of 3.7 seconds and the lowest packet loss of 0.1%.